IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS IV UPT SDN PANAIKANG II KOTA MAKASSAR - Mawaddah; Abdul Munir; M.Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Problem Based Learning (PBL) instructional model in improving students' critical thinking skills in the Indonesian language lessons for fourth-grade students at UPT SDN Panaikang II, Makassar City. This research uses a Classroom Action Research (CAR) approach, carried out in two cycles. Each cycle consists of the stages of planning, action implementation, observation, and reflection. The research subjects were the fourth-grade students of UPT SDN Panaikang II, Makassar City, totaling 25 students. Data collection techniques used include observation, tests, and documentation. The data were analyzed using quantitative descriptive analysis techniques with percentages to see the improvement in students' critical thinking skills. The results of the study show that the implementation of the problem-based learning model can improve students' critical thinking skills. In Cycle I, the evaluation results showed that 7 students, or 28%, reached the Minimum Competency Criteria (KKM), while 18 students, or 72%, had not yet met the KKM, with a class average score of 55. In addition, the observation results for critical thinking skills indicators scored 38 with a percentage of 63%. In Cycle II, there was a significant improvement, where the number of students reaching the KKM increased to 17 students or 68%, while the number of students not meeting the KKM decreased to 8 students or 32%, with a class average score of 74. The observation results for critical thinking skills indicators also increased to a score of 48 with a percentage of 80%. Based on these research results, it can be concluded that the implementation of the Problem-Based Learning model is effective in improving critical thinking skills in Indonesian language learning for fourth-grade students at UPT SDN Panaikang II, Makassar City.